2019
DOI: 10.1152/japplphysiol.01058.2018
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of 20% albumin fluid loading in healthy subjects: a comparison of four resuscitation fluids

Abstract: Recently, buffered salt solutions and 20% albumin (small volume resuscitation) have been advocated as an alternative fluid for intravenous resuscitation. The relative comparative efficacy and potential adverse effects of these solutions have not been evaluated. In a randomized, double blind, cross-over study of six healthy male subjects we compared the pulmonary and hemodynamic effects of intravenous administration of 30 ml/kg of 0.9% saline, Hartmann's solution and 4% albumin, and 6 ml/kg of 20% albumin (albu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 86 publications
2
11
0
Order By: Relevance
“…Our data are consistent with prior studies finding that administration of hyperoncotic albumin during surgery increases plasma volume has only a small effect on coagulation 3 and is "effective and safe." 4 The magnitude of the expansion we found was also similar to prior studies. Margarson and Soni 16 infused 20% albumin rapidly into volunteers and found a hemodilution corresponding to 2.1 times the infused volume; the albumin T 1/2 was 8.8 hours.…”
Section: Literaturesupporting
confidence: 90%
“…Our data are consistent with prior studies finding that administration of hyperoncotic albumin during surgery increases plasma volume has only a small effect on coagulation 3 and is "effective and safe." 4 The magnitude of the expansion we found was also similar to prior studies. Margarson and Soni 16 infused 20% albumin rapidly into volunteers and found a hemodilution corresponding to 2.1 times the infused volume; the albumin T 1/2 was 8.8 hours.…”
Section: Literaturesupporting
confidence: 90%
“…On the other hand, it has been demonstrated that the sole administration of large amounts of crystalloid fluids is suffice to raise systemic ANG-2 levels. This is independent of inflammatory activation but probably mediated by changes in endothelial shear stress [23][24][25]. In sum, in our patients, this resulted in a significant increase in the ANG-2/1 ratio throughout surgery.…”
Section: Discussionmentioning
confidence: 62%
“…Bolus infusion of 20% HSA solution is effective and safe in healthy subjects, as demonstrated in a randomized, doubleblind, cross-over study which compared the pulmonary and hemodynamic effects of commonly available crystalloid and colloidal solutions, i.e. 30 mL/kg of 0.9% saline, Hartmann's solution, 4% HSA solution, and 6 mL/kg of dose-equivalent 20% HSA solution 91 . Another study in healthy volunteers showed that infusion of 20% HSA solution significantly increased plasma volume by recruiting interstitial fluid 92 .…”
Section: Healthy Volunteersmentioning
confidence: 99%